ANALISIS PENERAPAN AKUNTANSI ZAKAT PADA LEMBAGA AMIL ZAKAT (LAZ) UNIT PENGUMPULAN ZAKAT (UPZ) KEMENTERIAN AGAMA KABUPATEN MALANG - Hikmah Fitri Kasalo; Afifudin Afifudin; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2020)
ABSTRACTThis study was conducted to analyze the application of zakat accounting to the zakat amil institutions (LAZ) of the Zakat Collection Unit (UPZ) Ministry of Religion in Malang, namely BAZNAS. The subjects in this study were LAZ Treasurer, Finance Staff, Finance Manager and Recognition. This type of research is a case study with descriptive analysis method based on primary data obtained by a combination of depth interviews, documentation, direct observation and secondary data. Based on the results of the analysis and discussion it has been concluded that the application of PSAK 109 in BAZNAS Malang Regency is not yet fully appropriate because the accounting process is in accordance with the accounting generally applied, the recognition and measurement of zakat funds do not recognize impairment of non-cash zakat as amil loses or deduction of zakat funds, recognition and measurement of infak/alms funds do not recognize impairment of non-cash infaq/alms as amil fund losses or deduction of infak funds, the disclosure does not make notes on the financial statements, but in the presentation is in accordance with PSAK 109.Keywords: Zakat Accounting, PSAK 109.